Finding a Way Out: A Study of the Female Image in Anna Christie - Yang, Zhen (Transactions on Social Science, Education and Humanities Research, 2023)
Anna Christie is the second play to win the great American playwright Eugene O ’Neill the Pulitzer Prize. The heroine Anna is oppressed in the patriarchal society. She leads a miserable life, and her self-consciousness and self-independence are gradually aroused. She resists the social injustice and inequality in her own way. Based on the novel text, this paper analyzes the image of Anna from the following aspects: the personality, the absence of paternal love and the awakening of self-consciousness, in a way to show the ability, the trigger and the process of Anna’s finding a way out.